Truth in Søren Aabye Kierkegaard and Augustine of Hippo: a new philosophical perspective - Morales Rojas, Arturo (Razón y fe, 2025)
Truth has been, without a doubt, one of the great concerns of philosophers throughout history. For this reason, the fundamental objective of this work is to carry out a hermeneutical tracing applied to the perceptions of Augustine of Hippo and Søren Aabye Kierkegaard, who, through their philosophical disquisitions, emit a new perspective on truth. Therefore, the novelty lies in the consideration of the relationship, as an ontological and anthropological place of truth, focusing attention on relevant issues such as interiority, self-choice and being-in-truth, as a thematic category key to their approaches. Likewise, this work provides a space for dialogue, in the Socratic sense, between both authors, causing the reader of the article to insert themselves into said conversation. Augustine, the philosopher of interiority in late antiquity, and Kierkegaard, the philosopher of existential singularity, present their points of view on the notion of truth, emphasizing, as a point in common, the relationship of the self before God, as place to be understood as singular truth.
Keywords: Augustine; Kierkegaard; interiority; relation; existence